Acquired Cystic Kidney Disease–associated Renal Cell Carcinoma (ACKD-RCC) Harbor Recurrent Mutations in KMT2C and TSC2 Genes. (November 2020) - Shah, Abhishek; Lal, Priti; Toorens, Erik; Palmer, Matthew B.; Schwartz, Lauren; Vergara, Norge; Guzzo, Thomas; Nayak, Anupma
Abstract : Individuals with acquired cystic kidney disease (ACKD) in the setting of end-stage renal disease (ESRD) have a high risk of developing renal cell carcinoma (RCC). ACKD-RCC is considered a distinct renal neoplasm in the International Society of Urologic Pathologists (ISUP)-World Health Organization (WHO) classification of kidney tumors which may behave aggressively. Since its original description, there have been multiple case reports and series published; however, the pathogenesis of this neoplasm is uncertain and there is limited data on the genetic aberrations of this tumor. Herein, we present our experience with ESRD kidneys, with emphasis on ACKD-RCC, associated cysts, and the somatic mutation analysis of a subset of ACKD-RCCs using next-generation sequencing. Our data on 59 cases with ESRD that underwent nephrectomy, shows that ACKD-RCC represents more than half of the tumors (25/46; 54%) developing in ESRD, followed by papillary RCC (13; 28%). History of dialysis, male sex, and African American race were potential risk factors for developing ACKD-RCCs. Further, ACKD-RCC–like cysts are possible precursors of RCCs in the ACKD setting noted in 40 of 46 (87%) cases with tumors. Next-generation sequencing analysis revealed recurrent mutations in the KMT2C gene in 4 of 5 ACKD-RCCs (80%), exclusively exhibiting cribriform "sieve-like" morphology; whereas the case negative for KMT2C mutations exhibited "type 2" papillary RCC morphology and lacked "sieve-like" growth pattern. Pathogenic mutations in TSC2 were the second common abnormality (3/5; 60%), often coexisting with KMT2C mutations. Deleterious mutations in additional genes such as CBL, PDGFRA, and SYNE1, etc. were noted but were nonrecurrent and always coexisted with mutations in KMT2C or TSC2 . To conclude, our study highlights that mutations in a chromatin-modifying gene KMT2C may potentially be oncogenic drivers for the development of ACKD-RCC with classic sieve-like morphology. In addition, pathogenic mutations in TSC2 possibly play a role in the development of cysts/tumors in a subset of ACKD patients. If corroborated in larger cohorts, these findings would be useful in planning surveillance and early intervention in ESRD patients developing ACKD.